Prospective quality control study of a novel gravity‐driven whole blood separation system suitable for humanitarian crises. Issue 8 (26th September 2017) - Hackstein, H.; Möller, A.; Gerlach, M.; Sachs, U.; Bein, G.
Abstract : Centrifugation‐based whole blood (WB) separation represents the worldwide standard but it depends on electricity and infrastructure. We have prospectively evaluated a novel hollow‐fibre WB separation system that does not require manual priming or blood flow regulation ( n = 29). RBC units contained sufficient Hb (50·4 g ± 4·3), low leucocytes (90 000 ± 0·008), exhibited low haemolysis (0·57% ± 0·49) and robust ATP content (51·47% ± 8·2) after 43 days storage. Plasma units contained low leucocytes and mean coagulation factor activities for FV, FVIII and FXI were 47%, 90% and 68%, respectively. RBC met quality specifications but plasma units exhibited reduced FV and FXI activity.